Overexpressing 3-hydroxy-3-methylglutaryl coenzyme A reductase (HMGR) in the lactococcal mevalonate pathway for heterologous plant sesquiterpene production. - Adelene Ai-Lian Song; Janna Ong Abdullah; Mohd Puad Abdullah; Norazizah Shafee; Roohaida Othman; Ee-Fun Tan; Normah Mohd Noor; Abdul Rahim Raha (PLoS ONE, 2012)
Isoprenoids are a large and diverse group of metabolites with interesting properties such as flavour, fragrance and therapeutic properties. They are produced via two pathways, the mevalonate pathway or the 2-C-methyl-D-erythritol-4-phosphate (MEP) pathway. While plants are the richest source of isoprenoids, they are not the most efficient producers. Escherichia coli and yeasts have been extensively studied as heterologous hosts for plant isoprenoids production. In the current study, we describe the usage of the food grade Lactococcus lactis as a potential heterologous host for the production of sesquiterpenes from a local herbaceous Malaysian plant, Persicaria minor (synonym Polygonum minus). A sesquiterpene synthase gene from P. minor was successfully cloned and expressed in L. lactis. The expressed protein was identified to be a β-sesquiphellandrene synthase as it was demonstrated to be functional in producing β-sesquiphellandrene at 85.4% of the total sesquiterpenes produced based on in vitro enzymatic assays. The recombinant L. lactis strain developed in this study was also capable of producing β-sesquiphellandrene in vivo without exogenous substrates supplementation. In addition, overexpression of the strain's endogenous 3-hydroxy-3-methylglutaryl coenzyme-A reductase (HMGR), an established rate-limiting enzyme in the eukaryotic mevalonate pathway, increased the production level of β-sesquiphellandrene by 1.25-1.60 fold. The highest amount achieved was 33 nM at 2 h post-induction.